Determination of Combustion Properties of Heat Treated Wood Materials - Ozcan, Cemal; Gündüz, Gökhan (My University, 2021)
Studies on heat-treated wood are mostly focused on physical and mechanical properties. There is no sufficient study on combustion properties of heat-treated wooden material. In this study, combustion properties of heattreated wooden material were determined. According to results of combustion, mass reduction in heat-treated wooden material less than non-heat-treated wood material. Temperature values of the heat-treated wooden material are higher than control samples. During combustion test, also, it was noticed that the amount of released gases such as carbon monoxide (CO), nitrogen oxide (NO) and oxygen (O2) values in heat-treated wooden material are higher than control ones in general.
Keywords: Malzeme Bilimleri; Kâğıt ve Ahşap; Orman Mühendisliği